Effect of follicular replacement (GnRH) and bovine somatotropin (bST) on the fertility of dairy cows exposed to heat stress - Lozano-Domínguez, Renato Raúl; Carrera Chavez, Jose Maria; Aréchiga Flores, Carlos Fernando; López Carlos, Marco Antonio; Cortés Vidauri, Zimri; Rincón Delgado, Melba; Macías Cruz, Ulises; Hernández Cerón, Joel (2020)
Three reproductive protocols were evaluated: 1) PG: injection of PGF2 on d-50 postpartum and insemination (AI) based on estrus detection. 2) OVS (Ovsynch: d 0, GnRH; d 7, PGF2; d 9, GnRH; d 10, AI); 3) ROV (GnRH + Ovsynch: d- 7, GnRH; d 0, GnRH; d 7 PGF2; d 9, GnRB; d 10, AI). In addition, the effect of somatotropin (bST) to AI, on fertility at first postpartum service (FERT), and pregnancy rate at 99 d postpartum (PP) FERT was similar in ROV and OVS (36.2 vs 36.6 %) (P>0.05); and higher than PG (27.3 %) (P<0.05). Likewise, FERT was similar with and without bST (36.2 vs 30.6 %, P>0.05). PG and without bST (22.5 %) was lower than OVS with (38.5 %) and without bST (33.7 %), as well as than ROV with (37.0 %) and without bST (36.1 %), and PG with bST (32.9 %). The pregnancy rate at 99 d was: OVS (60.6 %); ROV (54.3 %), higher than PG group (46.8 %) (P>0.05). OVS with (64.7 %) and without bST (56.5 %) and ROV without bST were higher than PG without bST (41.1 %, P<0.05). In conclusion, GnRH before Ovsynch (ROV) and bST at AI did not increase fertility at the first service in Holstein cows under heat stress. OVS and ROV increased fertility of first service postpartum and pregnancy rate to 99 d postpartum. Somatotropin increased fertility of first postpartum service only in PG treated cows.